Bone growth evaluation in collagen-hydroxyapatite implant locations using digital radiography: an animal model - Sari, Laela; Julia, Siti; Lubis, Lukmanda Evan; Sihono, Dwi Seno Kuncoro; Sari, Yessie Widya; Soejoko, Djarwani Soeharso (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Digital radiography has been used to evaluate the progress of bone growth with a collagen-hydroxyapatite implant in rabbit tibias. This study aimed to introduce digital radiography methods that provide comprehensive data availability for continuous information retrieval from the implant preparation to the cultivation period. METHODS 38 digital radiographs were divided into 3 treatment groups, namely a single defect without implant (control), single-implant, and three-implant. Radiographic acquisitions were performed at preparation time and post-implantation from 0 to 56 days. Observations were concentrated on the implantation site, followed by creating a lateral profile. The prediction of implantation growth was determined using relative bone density (RBD) percentage. RESULTS Based on the profile, the recovery process consisted of implant absorption and new bone tissue deposition. The absorption process was highly influenced by the defect size. In the control and single-implant groups, regardless of the different recovery processes, similar recovery results were observed 56 days post-implantation, with an RBD value of approximately 90%. Meanwhile, the three-implant group only had an RBD value of 62%. CONCLUSIONS Radiography can evaluate absorption and new bone growth during implantation in New Zealand white rabbits. Radiographs, which can be obtained at any time during cultivation, offered more information on the recovery implantation process than the other method that relies on data obtained after sacrificing the animals.